Savarkar and the making of Hindutva - Bakhle, Janaki (Princeton University Press, 2024)
"Vinayak Damodar Savarkar (1883-1966) was an intellectual, ideologue, and anticolonial nationalist leader in India's struggle for independence from British colonial rule, one whose anti-Muslim writings exploited India's tensions in pursuit of Hindu majority rule. Savarkar and the Making of Hindutva is the first comprehensive intellectual history of one of the most contentious political thinkers of the twentieth century. Janaki Bakhle examines the full range of Savarkar's voluminous writings in his native language of Marathi, from political and historical works to poetry, essays, and speeches. She reveals the complexities in the various positions he took as a champion of the beleaguered Hindu community, an anticaste progressive, an erudite if polemical historian, a pioneering advocate for women's dignity, and a patriotic poet. This critical examination of Savarkar's thought shows that Hindutva is as much about the aesthetic experiences that have been attached to the idea of India itself as it is a militant political program that has targeted the Muslim community in pursuit of power in postcolonial India.By bringing to light the many legends surrounding Savarkar, Bakhle shows how this figure from a provincial locality in colonial India rose to world-historical importance. Savarkar and the Making of Hindutva also uncovers the vast hagiographic literature that has kept alive the myth of Savarkar as a uniquely brave, brilliant, and learned revolutionary leader of the Hindu nation"-- Provided by publisher.
Keywords: Savarkar, Vinayak Damodar, -- 1883-1966.; Savarkar, Vinayak Damodar, -- 1883-1966; Nationalists -- India -- Biography.; Revolutionaries -- India -- Biography.; Intellectuals -- India -- Biography.; Hindutva.; Authors, Marathi -- 20th century -- Biography.; Indian intellectuals -- Biography.; Nationalistes -- Inde -- Biographies.; Révolutionnaires -- Inde -- Biographies.; Intellectuels -- Inde -- Biographies.; Intégrisme hindou.; Écrivains marathes -- 20e siècle -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY / Political.; RELIGION / Islam / History.; Authors, Marathi; Hindutva; Intellectuals; Nationalists; Revolutionaries; India; Biography & non-fiction prose.; Biography.; 1900-1999; Electronic books.; Biographies